Configurational landscape heterogeneity shapes functional community composition of grassland butterflies - Perović, David; Gámez‐Virués, Sagrario; Börschig, Carmen; Klein, Alexandra‐Maria; Krauss, Jochen; Steckel, Juliane; Rothenwöhrer, Christoph; Erasmi, Stefan; Tscharntke, Teja; Westphal, Catrin; Kleijn, David (The Journal of applied ecology, 2015)
Landscape heterogeneity represents two aspects of landscape simplification: (i) compositional heterogeneity (diversity of habitat types); and (ii) configurational heterogeneity (number, size and arrangement of habitat patches), both with different ecological implications for community composition. We examined how independent gradients of compositional and configurational landscape heterogeneity, at eight spatial scales, shape taxonomic and functional composition of butterfly communities in 91 managed grasslands across Germany. We used landscape metrics that were calculated from functional maps based on habitat preferences of individual species during different life stages. The relative effects of compositional and configurational landscape heterogeneity were compared with those of local land‐use intensity on butterfly taxonomic diversity, community composition and functional diversity of traits related to body size, feeding breadth and migratory tendency. As expected, compositional heterogeneity had strong positive effects on taxonomic diversity, while configurational heterogeneity had strong positive effects on trait dominance within the community. When landscapes had smaller mean patch size and greater boundary area, communities were dominated by species with more specialized larval feeding, decreased forewing length and limited migratory tendency. The positive effects of increased configurational landscape heterogeneity outweighed the negative effects of local land‐use intensity on larval‐feeding specialization, at all spatial scales, highlighting its importance for specialists of all dispersal capabilities. Synthesis and applications. We show that landscapes with high compositional heterogeneity support communities with greater taxonomic diversity, while landscapes with high configurational heterogeneity support communities that include vulnerable species (feeding specialists with larger body size, sedentary nature and more negatively affected by local management intensity). A decline in functional community composition can lead to functional homogenization, affecting the viability of the ecosystems by decreasing the variability in their responses to disturbance and altering their functioning. A landscape management for grasslands that promotes the maintenance of small patch sizes and a diversity of land uses in the surrounding landscape (within 250–1000 m) is recommended for the conservation of diverse butterfly communities. These strategies could also benefit government programmes such as the EU 2020 Biodiversity Strategy in their efforts to reduce the loss of biodiversity in agricultural landscapes.